Pengaruh Transformational Leadership dan Organizational Citizenship Behaviour Terhadap Organizational Performance melalui Workplace Spirituality sebagai Variabel Mediasi (Studi pada PT Wom Finance) - Pujiastuti, Mena; Tarumingkeng, Rudy C; Wahyoedi, Soegeng (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this study was to determine the effect of transformational leadership on workplace spirituality, organizational citizenship behavior on workplace spirituality, transformational leadership on organizational performance, organizational citizenship behavior on organizational performance, workplace spirituality on organizational performance, transformational leadership on organizational performance mediated by workplace spirituality, organizational citizenship behavior on organizational performance mediated by workplace spirituality. The number of respondents in this study were 88 respondents. SEM PLS analysis technique used with the help of SPSS. The result Transformational leadership has no effect on workplace spirituality. Organizational citizenship behavior has a significant positive effect on workplace spirituality. Transformational leadership has no effect on organizational performance. Organizational citizenship behavior has a significant positive effect on organizational performance Workplace spirituality.